ESSENTIAL IMPERATIVES AND MECHANISMS OF PUBLIC GOVERNANCE OF INFRASTRUCTURAL SUPPORT FOR REGIONAL ECONOMIC DEVELOPMENT (Regional aspects of productive forces development of Ukraine, 2026)
Introduction. The pivotal role of the infrastructure sector in shaping the institutional environment of the regional economy, along with the growing challenges to its development under wartime conditions, highlights the need to improve public governance of infrastructural support for regional economic development.Purpose. The study aims to explore the essential imperatives of public governance of infrastructural support for regional economic development and to define approaches for developing public management strategies to shape the regional infrastructure environment, taking into account current challenges.Research methods. The study employs methods of analysis and synthesis, systematization, structural-functional analysis, and generalization.Results. The role of infrastructural support in shaping the institutional environment for regional economic development has been substantiated. The key tasks for modernizing regional infrastructure are outlined. The necessity of developing adaptive management mechanisms to meet regional infrastructural challenges, taking into account their specific features, has been justified. The institutional basis of public governance for regional infrastructure development within a three-level strategic planning model has been defined. Target benchmarks serving as imperatives for developing public governance mechanisms of infrastructural support for regional economic development are presented. The tasks of regional infrastructure policy and approaches to their implementation have been identified.Conclusions. The development and implementation of public governance mechanisms for infrastructural support of regional economic development should be based on effective interaction between authorities at different levels. This approach would ensure the consideration of national, regional, and local interests, enable the fullest possible use of support from international institutions, and effectively engage the potential of territorial communities in the processes of regional infrastructure development.Keywords: Infrastructural support, public governance, regional economy, regional infrastructure, infrastructure sector.Formulas: 0, fig.: 0, tabl.: 0, bibl.: 10.